Requirement for binding multiple ATPs to convert a GroEL ring to the folding-active state - Chapman, Eli (National Academy of Sciences, 2008)
Production of the folding-active state of a GroEL ring involves initial cooperative binding of ATP, recruiting GroES, followed by large rigid body movements that are associated with ejection of bound substrate protein into the encapsulated hydrophilic chamber where folding commences. Here, we have addressed how many of the 7 subunits of a GroEL ring are required to bind ATP to drive these events, by using mixed rings with different numbers of wild-type and variant subunits, the latter bearing a substitution in the nucleotide pocket that allows specific block of ATP binding and turnover by a pyrazolol pyrimidine inhibitor. We observed that at least 2 wild-type subunits were required to bind GroES. By contrast, the triggering of polypeptide release and folding required a minimum of 4 wild-type subunits, with the greatest extent of refolding observed when all 7 subunits were wild type. This is consistent with the requirement for a “power stroke” of forceful apical movement to eject polypeptide into the chamber.